Batik Liquid Waste Management in the Batik Center Area of Tasikmalaya - Meylani, Vita; Mutiara, Frista; Hernawati, Diana (MAXIMUS: Journal of Biological and Life Sciences, 2023)
Batik production in Indonesia is increasing from year to year. However, regarding environmental quality, it is feared that it will produce waste that pollutes the surrounding water bodies. This study aims to describe problems and solutions in improving the management of batik liquid waste in the city and district of Tasikmalaya (Cipedes and Sukaraja) using descriptive qualitative methods and the Miles and Huberman model. The results of the research using interview and observation methods show that most batik SMEs in these two areas have been unable to manage waste optimally. The problem arising from batik liquid waste is the contamination of residents' fish ponds, sewers, and bathtubs. Although there are three independent and communal WWTPs (Wastewater Treatment Plants) in Cipedes (MSME Agnessa, Deden, and riverbanks) as well as one independent WWTP in UMKM Sukapura "GJM," their utilization is still constrained by various natural and artificial factors. The role of the surrounding community is still low in understanding the existence and impact of batik waste around them.